Clinical Presentation and Treatment Outcome of African Americans With Complicated Grief - Cruz, Mario (2007)
OBJECTIVE: This study sought to examine whether ethnic differences occur in the presentation of patients with complicated grief or their treatment outcome. METHODS: Analyses of a randomized controlled trial comparing a novel psychotherapy for complicated grief with interpersonal psychotherapy contrasted the clinical presentation, treatment alliance, and rates of treatment completion and response for 19 African Americans with complicated grief and 19 Caucasian Americans with complicated grief matched by sex, age, and baseline grief severity. Participants were randomly assigned to receive 16 sessions of either standard interpersonal psychotherapy or interpersonal psychotherapy enhanced with focused complicated grief components. RESULTS: No differences were found in any clinical or treatment-related measure. CONCLUSIONS: African Americans and Caucasian Americans with complicated grief did not differ significantly in clinical presentation, treatment alliance, treatment completion, and outcome. The results suggest that standard treatment for complicated grief can be provided successfully for different racial and economic groups.